Plasma Lipoproteins, Hemostasis and Thrombosis - Griffin, John H.; Fernández, José A.; Deguchi, Hiroshi (Thrombosis and Haemostasis, 2001)
Regulation of hemostasis and thrombosis involves numerous plasma factors that contribute to procoagulant and anticoagulant pathways. Lipid-containing surfaces provide sites where both procoagulant and anticoagulant enzymes, cofactors and substrates are assembled to express their activities. Plasma and lipoproteins can contribute to either procoagulant or anticoagulant reactions. Procoagulant lipids/lipoproteins include triglyceride-rich particles in plasma and oxidized low density lipoprotein (LDL) which can accelerate activation of prothrombin, factor X and factor VII. Potentially anticoagulant lipids and lipoproteins, each of which enhances inactivation of factor Va by activated protein C, include phosphatidylethanolamine, cardiolipin, the neutral glycosphingolipids glucosylceramide and Gb3 ceramide (CD77), and high density lipoprotein (HDL). Remarkably, treatment of hyperlipidemia with statins not only lowers lipids but also provides antithrombotic effects whose mechanisms remain to be clarified. We hypothesize that procoagulant and anticoagulant lipids and lipoproteins in plasma may contribute to a Yin-Yang balance that helps influence the up-regulation and down-regulation of thrombin generation.
Keywords: Lipoprotein; glycolipid; glucosylceramide; protein C; prothrombinase